2023
DOI: 10.3389/fphar.2023.1102581
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of curcumin in the treatment of colon cancer based on network pharmacology and molecular docking

Abstract: Objective: Curcumin is a plant polyphenol extracted from the Chinese herb turmeric. It was found that curcumin has good anti-cancer properties in a variety of cancers, but the exact mechanism is not clear. Based on the network pharmacology and molecular docking to deeply investigate the molecular mechanism of curcumin for the treatment of colon cancer, it provides a new research direction for the treatment of colon cancer.Methods: Curcumin-related targets were collected using PharmMapper, SwissTargetPrediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The binding energy is an indicator to assess the magnitude of the affinity between the ligand and the receptor. It has been shown that there is strong binding activity between ligand and receptor when the binding energy is less than −5.0 kcal/Mol ( He et al, 2023 ). In this study, the molecular docking results showed that the binding energies between Sorafenib and the target proteins were all less than −5.59 kcal/Mol ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy is an indicator to assess the magnitude of the affinity between the ligand and the receptor. It has been shown that there is strong binding activity between ligand and receptor when the binding energy is less than −5.0 kcal/Mol ( He et al, 2023 ). In this study, the molecular docking results showed that the binding energies between Sorafenib and the target proteins were all less than −5.59 kcal/Mol ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of molecular docking showed that the values of the docking energy of AE and candidate proteins were <0 ( Table 5 ), indicating that AE could spontaneously bind to the amino acids of target proteins without external assistance ( He et al, 2023 ). Among them, AKT1, TP53, ALB, ESR1, STAT3, CASP3, and EGFR had higher binding energy compared with their original ligands.…”
Section: Resultsmentioning
confidence: 99%
“…For the subsequent energy minimization step, the OPLS3e force field and optimization algorithm were engaged. To enhance convergence, a heavy atom root mean square deviation (RMSD) threshold of 0.30 Å was set, ensuring the optimization process was sufficiently precise [ 26 , 41 , 42 ].…”
Section: Software and Methodsmentioning
confidence: 99%